INTEGRATION OF SCIENCE IN SHAPING THE CHARACTER OF THE STUDENTS (From the Perpsective of Islamic Education) - Zein, Muhammad (Teknosains, 2019)
Religion and science cannot be separated from one to another. Both aspects rely on each other in order to develop. Constructively, the development of science and technology has led to the advance of the era in which has a positive impact to the human lives. Modern infrastructure like those on industrial facility, communication, and transportation simplify the mobility of the society.  This study explains about the integration of science in shaping the charters of the students in the perspective of Islam by using library research method. The library research method is also known as a the method of literature study.  The Islamic education in shaping the students' character in the competition of global era due to the impact of science and technology is very essential and cannot be denied from the social lives. In Islamic education, in order to achieve the success in the world than it has to be based on the science and vice versa. The Islamic education is a system which tries to implement the noble values of the students which include the aspects of knowledge, self –awareness, and application. Any activities that the teachers do should be able to influence the character of the students as a trigger to shape their personality. The Islamic education, in fact, has set the things relating to how the teachers behave, for instance, how they delivering their learning materials, tolerance, and some related matters. The purpose of this behavior is to shape the students to be a good human either in their society or country.